Time Till Viral Clearance of Severe Acute Respiratory Syndrome Coronavirus 2 Is Similar for Asymptomatic and Non-critically Symptomatic Individuals - Kumar, Nitya; AbdulRahman, AbdulKarim; AlAli, Salman; Otoom, Sameer; Atkin, Stephen L.; AlQahtani, Manaf (Frontiers in Medicine, 2021)
Despite the modeled estimations of the burden of asymptomatic spread, the duration of viral positivity and infectiousness of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains understudied. The objective of the present study was to estimate and compare the time till viral clearance of SARS-CoV-2 in asymptomatic and non-critical symptomatic individuals. We studied 184 SARS-CoV-2-positive participants, of whom 145 were asymptomatic. Our analysis uncovered that time till viral negativity is similar for subclinical [median time till viral clearance: 11 days, interquartile range (IQR): 8, 14] and overt infections (median: 11 days, IQR: 9, 14) after controlling for age and sex. This has implications in understanding the period of infectivity for SARS-CoV-2 in order to plan adequate public health measures to control the community spread.